MarcoPolo-R near earth asteroid sample return mission - Barucci, M.; Cheng, A.; Michel, P.; Benner, L.; Binzel, R.; Bland, Phil; Böhnhardt, H.; Brucato, J.; Campo Bagatin, A.; Cerroni, P.; Dotto, E.; Fitzsimmons, A.; et al. (Springer Netherlands, 2012)
MarcoPolo-R is a sample return mission to a primitive Near-Earth Asteroid (NEA) proposed in collaboration with NASA. It will rendezvous with a primitive NEA, scientifically characterize it at multiple scales, and return a unique sample to Earth unaltered by the atmospheric entry process or terrestrial weathering. MarcoPolo-R will return bulk samples (up to 2 kg) from an organic-rich binary asteroid to Earth for laboratory analyses, allowing us to: explore the origin of planetary materials and initial stages of habitable planet formation; identify and characterize the organics and volatiles in a primitive asteroid; understand the unique geomorphology, dynamics and evolution of a binary NEA. This project is based on the previous Marco Polo mission study, which was selected for the Assessment Phase of the first round of Cosmic Vision. Its scientific rationale was highly ranked by ESA committees and it was not selected only because the estimated cost was higher than the allotted amount for an M class mission.The cost of MarcoPolo-R will be reduced to within the ESA medium mission budget by collaboration with APL (John Hopkins University) and JPL in the NASA program for coordination with ESA’s Cosmic Vision Call. The baseline target is a binary asteroid (175706) 1996 FG3, which offers a very efficient operational and technical mission profile. A binary target also provides enhanced science return. The choice of this target will allow new investigations to be performed more easily than at a single object, and also enables investigations of the fascinating geology and geophysics of asteroids that are impossible at a single object. Several launch windows have been identified in the time-span 2020–2024. A number of other possible primitive single targets of high scientific interest have been identified covering a wide range of possible launch dates.The baseline mission scenario of MarcoPolo-R to 1996 FG3 is as follows: a single primary spacecraft provided by ESA, carrying the Earth Re-entry Capsule, sample acquisition and transfer system provided by NASA, will be launched by a Soyuz-Fregat rocket from Kourou into GTO and using two space segment stages. Two similar missions with two launch windows, in 2021 and 2022 and for both sample return in 2029 (with mission duration of 7 and 8 years), have been defined. Earlier or later launches, in 2020 or 2024, also offer good opportunities. All manoeuvres are carried out by a chemical propulsion system. MarcoPolo-R takes advantage of three industrial studies completed as part of the previous Marco Polo mission (see ESA/SRE (2009)3, Marco Polo Yellow Book) and of the expertise of the consortium led by Dr. A.F. Cheng (PI of the NASA NEAR Shoemaker mission) of the JHU-APL, including JPL, NASA ARC, NASA LaRC, and MIT.